Fundamental of Entrepreneurship ENT300 Old Taste Kopitiam / Sebestian Jief Gabriel Puem... [et.al] - Gabriel Puem, Sebestian Jief; Azmay @ Azhar, Asmuneerulizwan; Ramlee, Asiqa Shafiq; Atan, Mohd. Afiq (2011)
Our company name is Old Taste Kopitiam. The business has been decided on the form of four partnerships. Each partner has contribute certain amount of capital as agreed in our agreement. Our main business activity is to provide the best old taste of local foods to the public. We will open our restaurant at Matang Jaya, Kuching, Sarawak and hopefully will open by 1 st December 201 1 All partners are encourage and entitled to participate in all business management. We have agreed that SEBESTIAN JIEF is the General Manager and the Administration Manager. ASMUNEERULIZWAN BIN AZMAY @ AZHAR is the Operational Manager. ASIQA SHAFIQ is the Marketing Manager and MOHD. AFIQ BIN ATAN is the Financial Manager, The management team will be lead by the General Manager and the other manager will help in other process. The general manager is responsible in controlling, leading, organizing as well as plan the entire business. The administrative manager will responsible in doing for all jobs relating to office administration. The marketing manager will responsible in preparing the marketing process which includes the process of identifying the target market, determining the market size, identifying the competitors, determining the market share, developing the sales forecast and marketing strategies. The operation of our business is controlled and monitored by the operation manager. This is where quality control and productivity will take place in order to improve the efficiency of the workers. Finally, the financial manager will handle financial matters such as preparing for the budgets and financial statement for the each department. All the financial statement need to be taken care properly by our Finance manager.